2013
DOI: 10.1159/000350046
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal Disease in Chronic Kidney Disease and End-Stage Renal Disease Patients: A Review

Abstract: Periodontal disease is a chronic inflammatory disorder and being so it has been associated with accelerated atherosclerosis and malnutrition. Cardiovascular diseases are the leading cause of mortality in chronic kidney disease (CKD) and end-stage renal disease (ESRD) patients [National Institutes of Health, National Institute of Diabetes and Digestive and Kidney Diseases: Annual Data Report, 2010]. A recent scientific statement released by the American Heart Association [Lockhart et al.: Circulation 2012;125:2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 95 publications
(50 reference statements)
0
21
0
1
Order By: Relevance
“…Second, patients with periodontitis may prefer liquids over solids owing to discomfort, and this may also contribute to decreased nutritional status. Both could potentially be improved by increasing periodontal health (Ariyamuthu et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, patients with periodontitis may prefer liquids over solids owing to discomfort, and this may also contribute to decreased nutritional status. Both could potentially be improved by increasing periodontal health (Ariyamuthu et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Because of differing pathogenesis, periodontitis and end-stage renal disease (ESRD) were previously thought to be unrelated; the former is a localized infection caused by bacterial biofilm (Pihlstrom et al 2005), whereas the latter is a complete or almost complete failure of the kidneys (Levey et al 2005). However, more recently, evidence has indicated that these two conditions have much in common (Akar et al 2011, Ariyamuthu et al 2013, Ismail et al 2013. Cross-susceptibility between periodontitis and ESRD suggests a close two-way connection between them (de Souza et al 2007).…”
mentioning
confidence: 99%
“…Compared with healthy individuals, however, HD patients have higher susceptibility to infectious complications as a result of general deficiencies and a compromised immune system. This results in systemic changes as well as in oral complications. It is known that patients undergoing HD show worse oral conditions compared with healthy controls.…”
Section: Introductionmentioning
confidence: 99%
“…2 Epidemiological data reveal that 15% to 20% of the adult population has advanced chronic periodontitis, which might enhance susceptibility to systemic diseases such as diabetes, cardiovascular diseases, and stroke. [3][4][5][6] Therefore, early detection of periodontal disease is very critical to improve periodontitis treatment and reduce the occurrence of systemic diseases.…”
Section: Introductionmentioning
confidence: 99%